2008
DOI: 10.1002/gcc.20538
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone down‐regulates the tumor suppressor gene BRCA1 in mammary cells: A possible molecular link between stress and breast cancer

Abstract: Psychological stress has been correlated with breast cancer development in numerous epidemiological studies. However, physiological and molecular models which may account for this association are not readily available. We have found that the stress hormone hydrocortisone (cortisol) down-regulates the expression of the breast cancer susceptibility gene BRCA1 in the nonmalignant mouse mammary cell line EPH4. This effect is concentration-dependent, is reliant on the continuous presence of hydrocortisone, and is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 59 publications
(76 reference statements)
0
51
0
Order By: Relevance
“…Furthermore, specific studies have suggested that the cancer-causing effects of stress may be fairly specific to the breast (17,18). We previously presented the first molecular evidence for a connection between stress and breast cancer with our observation that BRCA1 expression is repressed by the synthetic stress hormone hydrocortisone in nonmalignant mouse mammary cells (19). This work was the first breast-specific molecular mechanism linking stress and breast cancer development.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Furthermore, specific studies have suggested that the cancer-causing effects of stress may be fairly specific to the breast (17,18). We previously presented the first molecular evidence for a connection between stress and breast cancer with our observation that BRCA1 expression is repressed by the synthetic stress hormone hydrocortisone in nonmalignant mouse mammary cells (19). This work was the first breast-specific molecular mechanism linking stress and breast cancer development.…”
Section: Introductionmentioning
confidence: 68%
“…The human breast carcinoma cell lines MCF-10A and MCF-7 were obtained from American Type Culture Collection. All cells were cultured as previously described (15,19). Cell treatments were completed using media lacking FBS or horse serum and containing either 1 mg/mL hydrocortisone (Sigma), 1, 5, or 10 mmol/L RU-486 (Sigma), or ethanol vehicle for 24 or 48 hours.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations